Biochar and its effects on plant productivity and nutrient cycling: a meta‐analysis. Issue 2 (31st December 2012) - Biederman, Lori A.; Harpole, W. Stanley
Abstract Biochar is a carbon‐rich coproduct resulting from pyrolyzing biomass. When applied to the soil it resists decomposition, effectively sequestering the applied carbon and mitigating anthropogenic CO2 emissions. Other promoted benefits of biochar application to soil include increased plant productivity and reduced nutrient leaching. However, the effects of biochar are variable and it remains unclear if recent enthusiasm can be justified. We evaluate ecosystem responses to biochar application with a meta‐analysis of 371 independent studies culled from 114 published manuscripts. We find that despite variability introduced by soil and climate, the addition of biochar to soils resulted, on average, in increased aboveground productivity, crop yield, soil microbial biomass, rhizobia nodulation, plant K tissue concentration, soil phosphorus (P), soil potassium (K), total soil nitrogen (N), and total soil carbon (C) compared with control conditions. Soil pH also tended to increase, becoming less acidic, following the addition of biochar. Variables that showed no significant mean response to biochar included belowground productivity, the ratio of aboveground : belowground biomass, mycorrhizal colonization of roots, plant tissue N, and soil P concentration, and soil inorganic N. Additional analyses found no detectable relationship between the amount of biochar added and aboveground productivity. Our results provide the first quantitative review of the effects of biochar on multiple ecosystem functions and the central tendencies suggest that biochar holds promise in being a win‐win‐win solution to energy, carbon storage, and ecosystem function. However, biochar's impacts on a fourth component, the downstream nontarget environments, remain unknown and present a critical research gap.